Hubungan antara pengetahuan keluarga tentang diit hipertensi dengan kekambuhan hipertensi pada lansia di posyandu Setya Budi desa Reksosari kecamatan Suruh Kabupaten Semarang - Puteh, Mis Musnee; , H.M Abi Muhlisin, SKM., M. Kep; , Kar t inah A. Kep., S. kep (2015)
Hypertension was a disease that classified as a silent killer. Hypertension was a disease that currently includes high and continues to rise, one of which caused non-adherent patients carry hypertension diet. Initial survey research on elderly Setya Budi elderly health center of Reksosari showed 7 of 9 elderly had a relapse, and most of the family members not understand about diet hypertension. The purpose of this study was to determine the relationship between knowledge about family relationships hypertension diet with recurrence of hypertension in the elderly in Setya Budi neighborhood health center of Reksosari Suruh Semarang. That study was a descriptive correlative study with cross-sectional design. The sample was 46 elderly family members who had hypertension in the elderly Setya Budi neighborhood health center of Reksosari Suruh Semarang with simple random sampling technique. The data processing techniques used Spearman Rank technique. Based on the results of research and discussion, the conclusions of this study were: (1) knowledge of the family of hypertension as a major diet was moderate category, (2) the recurrence rate of hypertension in the elderly mostly in the category often recur, and (3) there was a significant relationship between the level of knowledge about diet hypertension families with recurrence of hypertension in the elderly in Setya Budi neighborhood health center of Reksosari Suruh Semarang.